Ideal vs reality: evidences from senior teachers’ experiences on the Malaysian School-Based Assessment System (SBA) - Hashim, Che Noraini; Ariffin, Adlina; Muhd Hashim, Nurhidayah (IIUM Press, 2014)
School-based assessment (SBA) approach was officially introduced by the Ministry of Education as a part of the Malaysia educational reform in 2011 with the aim to improve the fairness of the education system when it is applied as a form of measurement of students’ academic progress. Under the system, students’ learning outcomes will be evaluated based on their ability and readiness and teachers are encouraged to use various evaluation methods such as question and answer sessions, quizzes, short writing, dramas, and role-playing (Dietel, Herman & Knuth, 1991; Davison, 2007). However, the system received great criticism since its implementation posed a great pressure on not only the teachers but also students as well as parents. This study aspires to investigate the issue of SBA based on evidences revealed by senior teachers from five secondary schools who were involved in the implementation of the system. This qualitative case study aims at identifying some perceptions, expectations and suggestions to improve the SBA. These senior teachers questioned the validity and reliability of the system as a fair measure in evaluating the academic progress of their students. They perceived SBA as an “imposed burden” in terms of additional paper work on teachers by educational authorities. Furthermore, some features of the Malaysian secondary school such as large class size and lack of supporting resources (e.g. internet facilities) had further aggravated their negative perceptions on the SBA system. Overall, they were confident that both students and teachers did not gain much benefit from the system. The findings indicated that for SBA to be successful, teachers must be given sufficient and detailed information on this new evaluation system. In doing so, their fears shall be allied and their negative attitudes shall be changed. Besides that, the teaching hours and class size need to be reduced. Once all these issues are looked into, it will lead to better implementation of the system.